Motets, Te Deum, Missa surrexit pastor - Hellinck, Lupus 1495-1541; Lupi, Johannes 1506-1539 (Hyperion Records, 2020)
Mining the rich musical seam of the low countries, Stephen Rice and The Brabant Ensemble have once again unearthed sixteenth-century treasure in the works of Lupus Hellinck and Johannes Lupi. - Midwesttape.com
Haupttitel von Behältnisvorderseite
Aufnahme: Parish Church of St John the Baptist, Loughton, Essex, United Kingdom, on 24-26 January 2019
Keywords: Masses; Motets; Sacred music; Choruses, Sacred (Mixed voices); Choruses, Sacred (Mixed voices, 4 parts), Unaccompanied; CD